2012
DOI: 10.1007/s12021-012-9161-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systems-Level Approach to Human Epileptic Seizures

Abstract: Epileptic seizures are due to the pathological collective activity of large cellular assemblies. A better understanding of this collective activity is integral to the development of novel diagnostic and therapeutic procedures. In contrast to reductionist analyses, which focus solely on small-scale characteristics of ictogenesis, here we follow a systems-level approach, which combines both small-scale and larger-scale analyses. Peri-ictal dynamics of epileptic networks are assessed by studying correlation withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 66 publications
(64 reference statements)
2
46
0
1
Order By: Relevance
“…Prior work has explored differences in seizure semiology to describe primary and secondary zones of dysfunction (Nair et al, 2004; Rosenow and Luders, 2001). Others have identified strong, tightly connected network hubs localized in areas outside of the seizure-generating region that indicate a wider extent of network damage (Rummel et al, 2013; Schevon et al, 2007; Zaveri et al, 2009). Our results support the view that tissue surrounding the seizure-generating area displays abnormalities that support seizure evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work has explored differences in seizure semiology to describe primary and secondary zones of dysfunction (Nair et al, 2004; Rosenow and Luders, 2001). Others have identified strong, tightly connected network hubs localized in areas outside of the seizure-generating region that indicate a wider extent of network damage (Rummel et al, 2013; Schevon et al, 2007; Zaveri et al, 2009). Our results support the view that tissue surrounding the seizure-generating area displays abnormalities that support seizure evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work at the cellular level indicates that seizure generation is complex, involving interactions between many neuronal subtypes both within and surrounding seizure-generating regions (Toyoda et al, 2015; Truccolo et al, 2011). Studies establishing a link between macroscale network structure and microscale neuroarchitectonics have demonstrated that heterogeneity of macroscale structure, such as regions of high and low node strengths often associated with the seizure-onset zone (Khambhati et al, 2015; Rummel et al, 2013; Schevon et al, 2007; Warren et al, 2010; Zaveri et al, 2009), is related to increasing complexity in the morphological structure of pyramidal neurons, a common post-synaptic site of excitatory neural activity (Scholtens et al, 2014; van den Heuvel et al, 2015). Prior work has demonstrated that strong γ-band activity at the site of interneurons can transition to β-band activity that is mediated by excitatory, pyramidal neuron activity through changes in excitatory synapses and potassium conductance (Kopell et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is the presence of functional heterogeneity in the cortical networks, represented by the lack of spatial slow wave homogeneity,[50,149] that seems to represent the necessary condition for seizure initiation during sleep (Figure 5-B and -C) [139,141]. Altogether, these findings suggests that from circumscribed bursts of low voltage fast activity inside the FCD only propagates and develop into a full blown seizure when the EZ (re)integrates collective brain dynamics during periods of functional heterogeneity [7,124,150]. Of note, such a state occurs spontaneously every night (phase A of the CAP)[115] and can also be triggered…”
mentioning
confidence: 92%
“…Here, the disturbance of these mapped circuits may be assessed using the technique of recording neuronal activity in local brain areas, called electroencephalography ( EEG) . EEG allows to obtain a good temporal resolution when measuring brain activity during epileptic seizures [ 167 ], or permits longitudinal tracking of the disruption of disease-relevant brain circuits, as shown for PD [ 168 ].…”
Section: Identifi Cation and Connecting Of Candidate Areasmentioning
confidence: 99%